Maximal heart rate differs between laboratory and field conditions among female athletes - Coutinho, C.; Watson, A.; Brickson, S.; Sanfilippo, J. (Journal of Human Sport & Exercise, 2017)
The purpose of this study was to determine if maximal heart rate (MHR) varies between laboratory testing, field testing, training, competitive matches and an agepredicted MHR equation among female collegiate soccer players. 21 female NCAA Division 1 soccer players had MHR determined during a maximal treadmill test (MHRGXT), a 20-meter shuttle run test (MHRFIELD), 4 weeks of early season training (MHRTRAIN), 5 competitive matches (MHRMATCH), and an age prediction equation (MHRPRED). Participants were excluded if they were injured during the data collection period or failed to obtain at least 2 out of 3 criteria during treadmill testing: 1) RER = 1.1, 2) plateau in VO2, and 3) attainment of =90% of MHRPRED. MHR was compared across different methods by ANOVA and Spearman correlation coefficients were determined between the different methods. 15 athletes satisfied the inclusion criteria. MHRGXT (190 ± 3.1 bpm) was significantly lower than MHRFIELD (197.9 ± 7.0 bpm, p<0.001), MHRTRAIN (198.9 ± 5.3bpm, p<0.001), and MHRMATCH (196.8 ± 4.4bpm, p=0.004), but not MHRPRED (193.8 ± 0.7bpm, p=0.12). Significant correlations were found between MHRGXT and MHRFIELD(r=0.89, p<0.001), MHRTRAIN (r=0.822, p<0.001), and MHRMATCH (r=0.584, p=0.02). No differences were identified between MHRFIELD, MHRTRAIN, or MHRMATCH, but all three measures were significantly correlated (r=0.63 to 0.81). MHRPRED was not significantly correlated with any of the other methods (r=-0.216 to 0.137). MHR from laboratory testing was significantly lower than field testing, training, and Powered by Editorial Manager® and ProduXion Manager® from Aries Systems Corporation competition, although all 4 methods were highly correlated. The differences in these methods should be taken into account when using MHR to prescribe exercise intensity.